Teaching and building. Temporary Architecture between research and didactics - Marco Imperadori; Federica Brunone (Agathón)
The development of digital design technologies offers undoubted teaching tools for design and planning: project, pro-jectare, throwing forward. Parametric design, BIM, augmented reality are now present in vocabulary and professional skills, but they often create a detachment from reality and materiality. The architecture, the unique and real one, is the built one, in which the material and spatial essences demonstrate whether the theoretical assumptions are valid or not. Imagining educational paths that lead students to create real artefacts is an innovative, unusual approach that combines educational research with applied research. The article outlines a path of collaboration among various institutions and tracks the premises, methodologies, and results, proposing future research developments and offering opportunities for dissemination, replication and dissemination.